2020
DOI: 10.1007/s40273-020-00967-7
|View full text |Cite
|
Sign up to set email alerts
|

Budget Impact of Oral Semaglutide Intensification versus Sitagliptin among US Patients with Type 2 Diabetes Mellitus Uncontrolled with Metformin

Abstract: Background Oral semaglutide was approved in 2019 for blood glucose control in patients with type 2 diabetes mellitus (T2DM) and was the first oral glucagon-like peptide 1 receptor agonist (GLP-1 RA). T2DM is associated with substantial healthcare expenditures in the US, so the cost of a new intervention should be weighed against clinical benefits. Objective This study evaluated the budget impact of a treatment pathway with oral semaglutide 14 mg daily versus oral sitagliptin 100 mg daily among patients not ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The discounting rate was not always clearly reported in the included BIA studies. Four studies reported the discounting rate ranging from 3 to 5% (16,(23)(24)(25), eight studies (11,15,(17)(18)(19)(20)(21)27) did not consider the discounting rate in compliance with the ISPOR Task Force guidelines (7). Meanwhile, six studies (10, 12-14, 22, 26) did not mentioned the discounting rate in the articles.…”
Section: Methodology and Budget Results Of Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…The discounting rate was not always clearly reported in the included BIA studies. Four studies reported the discounting rate ranging from 3 to 5% (16,(23)(24)(25), eight studies (11,15,(17)(18)(19)(20)(21)27) did not consider the discounting rate in compliance with the ISPOR Task Force guidelines (7). Meanwhile, six studies (10, 12-14, 22, 26) did not mentioned the discounting rate in the articles.…”
Section: Methodology and Budget Results Of Biasmentioning
confidence: 99%
“…Seven studies only calculated treatmentrelated costs only (10,(13)(14)(15)(21)(22)(23). Eleven studies took into account both treatment-related costs and condition-related costs (11,12,(16)(17)(18)(19)(20)(24)(25)(26)(27), of which nine studies considered the cost of hypoglycemia which was further classified into minor and severe hypoglycemia (11,12,16,18,20,(24)(25)(26)(27), six studies considered the cost of diabetes-related complications (11,16,17,19,25,27) (mainly including myocardial infarction (MI), stroke, heart failure, heart disease) and only one took the cost of adverse event (including dizziness, vomiting, fatigue and loss of appetite) into account (12).…”
Section: Methodology and Budget Results Of Biasmentioning
confidence: 99%
See 3 more Smart Citations